2020
DOI: 10.1128/mra.01286-19
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Four Pseudomonas aeruginosa Clinical Strains with Various Biofilm Phenotypes

Abstract: Biofilms produced by Pseudomonas aeruginosa present a serious threat to cystic fibrosis patients. Here, we report the draft genome sequences of four cystic fibrosis isolates displaying various mucoid and biofilm phenotypes. The estimated average genome size was about 6,255,986 ± 50,202 bp with a mean G+C content of 66.52 ± 0.06%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…An alternative hypothesis is that the architecture of the biofilm, rather than the organization of the ami operon, may explain the strain specific differences in OSTN susceptibility. Indeed, characterization of the clinical strains selected in the panel demonstrated that they form biofilms with significant differences in biofilm spatial organization and matrix composition [ 50 , 71 ]. Moreover, it was recently observed that P. aeruginosa PA14 exposed to hANP modifies the exopolysaccharides composition of the biofilm matrix [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative hypothesis is that the architecture of the biofilm, rather than the organization of the ami operon, may explain the strain specific differences in OSTN susceptibility. Indeed, characterization of the clinical strains selected in the panel demonstrated that they form biofilms with significant differences in biofilm spatial organization and matrix composition [ 50 , 71 ]. Moreover, it was recently observed that P. aeruginosa PA14 exposed to hANP modifies the exopolysaccharides composition of the biofilm matrix [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa PAK strain is a non-mucoid clinical strain [ 49 ]. Strains MUC-N1, MUC-N2, MUC-P4, MUC-P5 [ 50 ] are clinical isolates collected from sputum of CF patients (Nantes hospital) as well as CF6.14 (CNR Besançon, France). Finally, the clinical strains PAL 0.1 and PAL 1.1 [ 51 ] were isolated from the respiratory tract of a patient in intensive care unit (Lille hospital, France).…”
Section: Methodsmentioning
confidence: 99%
“…P. aeruginosa MUC-N1 is a mucoid clinical isolated from a cystic fibrosis patient at the Nantes teaching hospital [ 28 , 37 ]. P. aeruginosa MUC N1 was grown at 37 °C in Luria-Bertani medium (NaCl 10 g/L, tryptone 10 g/L, and yeast extract 5 g/L) under orbital shaking (125 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…[ 71 ] The MUC‐N1, MUC‐N2, MUC‐P4, and MUC‐P5 P. aeruginosa strains were isolated from sputum samples of adult cystic fibrosis patients followed at the Centre de Référence Contre la Mucoviscidose (CRCM), Centre Hospitalier Universitaire (CHU) of Nantes (France). [ 72 ] The P. aeruginosa clinical strains CF 8.19, CF 9.19 were isolated from sputum of cystic fibrosis patients (CF 8.19 and CF 9.19) (CNR résistance aux antibiotiques CHU Besançon, France). PAL 0.1 and PAL 1.1 were isolated from the airways of an intensive care unit (ICU) patient (Lille CHU hospital, France), with ventilator‐associated pneumonia (PAL1.1), or isolated from blood cultures of an ICU patient with sepsis PAL0.1.…”
Section: Methodsmentioning
confidence: 99%